Development of Independent Curriculum Printable Modules Pancasila Education Subject Class V SD Nurul Islam Cileungsi - Rio Ardi; Nurdin Ibrahim; Dedi Supriadi (Indonesian Journal of Pedagogy and Teacher Education, 2024)
This study aims to develop learning media in the form of printed modules for the Merdeka Curriculum in the fifth grade Pancasila Education subject at SD Nurul Islam, Bogor Regency. This research uses a combination of the Borg and Gall development model with Rowntree which results in a development model with the following steps; preliminary study, planning, writing preparation, initial draft development, initial trial, revision of trial results, main product field test, product revision, wide-scale field trial, final product revision and module dissemination and implementation. The feasibility test uses the validation of material experts, media experts and instructional design experts and considers the results of the user test of students and teachers.  The material experts' feasibility test yielded results of 91%, the media design experts' 90%, the instructional design experts' 87%, the student users' 94%, and the instructor users' 94%. received the designation of "extremely feasible" overall. These findings suggest that using printed modules to enhance the learning outcomes of fifth-grade Pancasila Education pupils at Nurul Islam Elementary School is rather practical. According to the study of the pretest and posttest findings, students' average pretest score was 55, their average posttest score was 91, and their highest average score was 100. The effectiveness test yielded a value of 0.8 in the high category, or percented to 80, based on the N-Gain score formula findings. A conversion level of > 76 indicates that the N-Gain score attainment level is considered effective. Therefore, using the Merdeka curriculum print module helps students in class V at Nuurl Islam Elementary School achieve better learning results in Pancasila Education courses. Based on these findings, it can be concluded that the development of the Merdeka curriculum print module in Pancasila Education subjects in grade V SD Nurul Islam is feasible and effective to use.